Factors associated with cognitive impairment and the quality-of-life among COVID-19 survivors working as healthcare workers - Sirait, Sondang RA.; Sinaga, Bintang YM.; Tarigan, Amira P.; Wahyuni, Arlinda S. (Narra J, 2024)
Prolonged physical and mental health changes, known as post-COVID conditions (PCC), could impair the quality-of-life (QoL) of healthcare workers. The aim of this study was to identify factors that contribute to cognitive impairments and QoL among COVID-19 survivors working as healthcare workers. This cross-sectional study involved healthcare workers at Prof. Dr. Chairuddin P. Lubis Universitas Sumatera Utara Hospital, Medan, Indonesia. The Montreal Cognitive Assessment (MoCA) was used to assess the cognitive function, while the World Health Organization Quality-of-Life Brief Version (WHOQOL-BREF) questionnaire was used to evaluate the QoL. Factors associated with cognitive and QoL status were examined using Mann-Whitney and Chi-squared tests. A total of 100 COVID-19 survivors were included in the study, most of whom were female (74%), aged ≤35 years (95%), and were doctors (62%). Only 22% of the participants had a normal BMI, 93% had a history of mild COVID-19, and 54% had one comorbidity. The Overall MoCA score averaged 24.18±2.86, indicating mild cognitive impairment among the groups. The distribution of MoCA scores had similar patterns with no significant differences based on age, gender, comorbidities, BMI, COVID-19 severity, and frequency of infection. Interestingly, the number of vaccine doses received by the participants had a statistically significant associated with MoCA scores of which those receiving more than two doses had higher cognitive scores than those with only two doses (p=0.008). Based on categorized MoCA scores (normal vs cognitive impairment), none assessed factors were not significantly associated with cognitive outcomes. The WHOQOL-BREF scores ranged from 62.5 to 95.5, with a mean of 83.67±7.03. None of the assessed factors were associated with WHOQOL-BREF scores among COVID-19 survivors. These findings highlight the need for further study to explore the protective role of vaccination frequency in cognitive impairment and the factors underlying the resilience in QoL among survivors.